KARAKTERISTIK DAN PEMILIHAN MEDIA PEMBELAJARAN DALAM E-LEARNING - Tafqihan, Zuhdi (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
The development of information technology recently has changed the paradigm of the community in seeking and obtaining information, in which it is no longer limited only to the information of newspapers, audio-visual and electronic, but also other sources of information such as Internet. It is generally understood that education is a process of delivering information from educators to learners. In this regard, educators are as sources of information, the media is as a means of learning aids to presenting theÂ  materials and students is as recipients of information. In its development, those three elements are assisted by information technology. Hence, it is issued the ideas about e-learning as an important component of the concept of distance learning. In order to determine the appropriate learning media for e-learning, there are some important things that should be paid attention, such as (1) identifying the knowledge and skills towards the learners and teachers, (2) ease of evaluation and assessment, (3) level of interaction between faculty members and students, (4) learning strategies, (5) the complexity of the materials and (6) dynamic change of the materials. Therefore, the use of media in e-learning must be occupied properly in order that the materials or content can be delivered properly.ØªØ·ÙÙØ± ØªÙÙÙÙÙØ¬ÙØ© Ø§ÙØ£Ø®Ø¨Ø§Ø± ÙÙ Ø§ÙØ³ÙÙØ§Øª Ø§ÙØ£Ø®ÙØ±Ø© ÙØºÙÙØ± Ø·Ø±ÙÙØ© ØªÙÙÙØ± Ø§ÙÙØ¬ØªÙØ¹ ÙÙ Ø§ÙØ¨ØØ« Ø¹Ù Ø§ÙÙØ¹ÙÙÙØ§Øª ÙØ§ÙØØµÙÙ Ø¹ÙÙÙØ§Ø Ø®Ø§Ø±Ø¬ Ø¹Ù Ø§ÙØ£Ø®Ø¨Ø§Ø± ÙØ§ÙÙØ¹ÙÙÙØ§Øª ÙÙ Ø§ÙØ¬Ø±Ø§Ø¦Ø¯ ÙØ§ÙØªÙÙØ§Ø² ÙØ§ÙØ£Ø¬ÙØ²Ø© Ø§ÙØ§ÙÙØªØ±ÙÙÙØ© Ø§ÙØ£Ø®Ø±Ù. ÙÙØ¬Ø£ Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙØ¢Ù Ø¥ÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙØ§ÙØªØ±ÙØª. ÙÙÙØ§ ÙÙ ÙØ¹ÙÙÙØ Ø£Ù Ø§ÙØªØ±Ø¨ÙØ© ÙÙ Ø¹ÙÙÙØ© Ø§ÙØµØ§Ù Ø§ÙÙØ¹ÙÙÙØ§Øª ÙÙ Ø§ÙÙØ¯Ø±Ø³ Ø¥ÙÙ Ø§ÙØ·ÙØ§Ø¨Ø ÙÙÙÙÙ Ø§ÙÙØ¯Ø±Ø³ ÙÙØ¨Ø¹ Ø§ÙÙØ¹ÙÙÙØ§ØªØ ÙØ§ÙÙØ³Ø§Ø¦Ù Ø£Ø¯Ø§Ø© ÙØ§ÙØµØ§ÙÙØ§Ø Ø«Ù Ø§ÙØ·ÙØ§Ø¨ ÙÙ Ø§ÙÙØ§Ø¨ÙÙÙ ÙÙÙØ¹ÙÙÙØ§Øª.ÙÙÙ ØªØ·ÙÙØ±ÙØ§ Ø¯Ø®Ù ÙÙÙØ§ ÙØ³Ø§Ø¦Ù ØªÙÙÙÙÙØ¬ÙØ© Ø§ÙØ£Ø®Ø¨Ø§Ø± ØØªÙÙ ØªÙÙÙØ¯ ÙÙÙØ§ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ§ÙÙØªØ±ÙÙÙØ ÙÙÙ Ø¹ÙØµØ± ÙØ§ÙÙ ÙÙ ÙÙÙÙÙ Ø§ÙØªØ¹ÙÙÙ Ø¹Ù Ø¨Ø¹Ø¯. ÙÙØªØ¹ÙÙÙ ÙØ³Ø§Ø¦Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙÙØ§Ø³Ø¨Ø© ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ§ÙÙØªØ±ÙÙÙ ÙØ§Ø¨Ø¯ ÙÙ Ø§ÙØ§ÙØªÙØ§Ù Ø¨Ø§ÙØ£ÙÙØ± Ø§ÙØ¢ØªÙØ© : (1) ØªØ´Ø®ÙØµ Ø§ÙÙØ¹ÙÙÙØ§Øª ÙØ§ÙÙÙØ§Ø±Ø§Øª Ø¹ÙØ¯ Ø§ÙÙØ¯Ø±ÙØ³ÙÙ ÙØ§ÙØ¯Ø§Ø±Ø³ÙÙ (2) Ø§ÙØ³ÙÙÙØ© ÙÙ Ø¹ÙÙÙØ© Ø§ÙØªÙÙÙÙ (3) ÙØ±ØÙØ© Ø§ÙØªØ¹Ø§ÙÙ Ø¨ÙÙ Ø§ÙØ¯Ø§Ø±Ø³ ÙØ§ÙÙØ¯Ø±Ø³ (4) Ø·Ø±Ù Ø§ÙØªØ¯Ø±ÙØ³ ÙØ£Ø³Ø§ÙÙØ¨ÙØ§ (5) ØªØ¹ÙÙØ¯ Ø§ÙÙØ§Ø¯Ø© (6) ØªØºÙÙØ± Ø§ÙÙÙØ§Ø¯ Ø§ÙÙØ³ØªÙØ±Ù . ÙÙÙØ°Ø§ ÙØ§Ø¨Ø¯ ÙÙ Ø§Ø®ØªÙØ§Ø± ÙØ³Ø§Ø¦Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙÙØ§Ø³Ø¨Ø© ÙØªÙØ¯ÙÙ Ø§ÙÙØ§Ø¯Ø© ØªÙØ¯ÙÙØ§ Ø¬ÙÙØ¯Ø§.Â Â  Â Â Â